Lung abscesses in children: A case report - Kriangburapa , Warawut; Siriboriruk , Jukrapun (Burapha Journal of Medicine, 2024)
Introduction: Because lung abscesses are uncommon in children, not a lot of information is available about this condition. However, it remains a severe respiratory condition. Objective: To describe the clinical manifestations, chest X -ray and, CT scan findings, and the management of children with lung abscesses. Case presentation: This retrospective descriptive study collected data from the medical records of two patients admitted to Burapha University Hospital between May 2021 and July 2022. The, two children had lung abscesses. Commonly presented symptoms include fever, rhinorrhea, diarrhoea, and vomiting. The diagnosis was established by chest radiographs and a CT scan. The locations of the lung abscesses were in the right lower lobe. Empiric intravenous antibiotics were the initial treatment for the lung abscesses. However, the patient didn’t respond to antibiotics in one case, leading us to perform percutaneous drainage. Subsequent pus analysis using polymerase chain reaction (PCR) identified Aggregatibacter segnis as the causative organism. Encouragingly, both cases achieved full recovery following treatment. Conclusion: Early clinical manifestations in children can pose challenges in diagnosing lung abscesses. A lack of awareness of lung abscesses may lead to a delayed diagnosis and treatment. Appropriate intravenous antibiotics are recommended as the initial treatment for lung abscesses in children. With a timely diagnosis and appropriate treatment, lung abscesses in children have a favourable prognosis.